Pengetahuan Etno-Didaktik Matematika Melayu Guru Sekolah Dasar di SDN 003 Kandis: Survei Pendahuluan Pelaksanaan Pengabdian kepada Masyarakat - Putra, Zetra Hainul; Hermita, Neni; Alim, Jesi Alexander; Witri, Gustimal; Deswita, Leli; Andhi, Rahmat Rizal; Sari, Intan Kartika; Gunawan, Yahya; Cahyani, Atik Luthfia (Unri Conference Series: Community Engagement, 2024)
Cultural integration in mathematics learning is one of the learning approaches that must be possessed by elementary school teachers in Indonesia. However, many teachers still have difficulty in integrating it. Therefore, it is necessary to design community service activities that can support elementary school teachers' knowledge of ethno-didactic of mathematics. The initial step taken was to measure teachers’ knowledge of ethno-didactic of mathematics by providing a survey to 16 teachers from SDN 003 Kandis. The teachers were given 5 statements related to their understanding of ethno-didactics of mathematics on a scale of 1 (poor) to 10 (excellent). The results of this initial survey indicate that teachers’ knowledge of ethno-didactic of mathematics is still in the low category, so it is necessary to conduct a workshop to strengthen the competence of elementary school teachers’ knowledge of ethno-didactics of mathematics and be able to use it in designing mathematics learning in elementary schools.